Answer:
(- 97, - 52)
Explanation:
given the 2 equations
x - 4y = 111 → (1)
2y - x = - 7 → (2)
Rearrange (1) expressing x in terms of y by adding 4y to both sides
x = 111 + 4y → (3)
Substitute x = 111 + 4y into (2)
2y - (111 + 4y ) = - 7 ← distribute and simplify left side
2y - 111 - 4y = - 7
- 2y - 111 = - 7 ( add 111 to both sides )
- 2y = 104 ( divide both sides by - 2 )
y = - 52
Substitute y = - 52 into (3) for corresponding value of x
x = 111 + 4(- 52) = 111 - 208 = -97
Solution is ( - 97, - 52 )